Chest radiography findings of COVID-19 pneumonia: a specific pattern for a confident differential diagnosis. (December 2022) - Landini, Nicholas; Colzani, Giulia; Ciet, Pierluigi; Tessarin, Giovanni; Dorigo, Alberto; Bertana, Luca; Felice, Carla; Scaldaferri, Luca; Orlandi, Martina; Nardi, Cosimo; Romagnoli, Micaela; Saba, Luca; et al.
Background: Chest radiography (CR) patterns for the diagnosis of COVID-19 have been established. However, they were not ideated comparing CR features with those of other pulmonary diseases. Purpose: To create the most accurate COVID-19 pneumonia pattern comparing CR findings of COVID-19 and non-COVID-19 pulmonary diseases and to test the model against the British Society of Thoracic Imaging (BSTI) criteria. Material and Methods: CR of COVID-19 and non-COVID-19 pulmonary diseases, admitted to the emergency department, were evaluated. Assessed features were interstitial opacities, ground glass opacities, and/or consolidations and the predominant lung alteration. We also assessed uni-/bilaterality, location (upper/middle/lower), and distribution (peripheral/perihilar), as well as pleural effusion and perihilar vessels blurring. A binary logistic regression was adopted to obtain the most accurate CR COVID-19 pattern, and sensitivity and specificity were computed. The newly defined pattern was compared to BSTI criteria. Results: CR of 274 patients were evaluated (146 COVID-19, 128 non-COVID-19). The most accurate COVID-19 pneumonia pattern consisted of four features: bilateral alterations (Expß=2.8, P =0.002), peripheral distribution of the predominant (Expß=2.3, P =0.013), no pleural effusion (Expß=0.4, P =0.009), and perihilar vessels' contour not blurred (Expß=0.3, P =0.002). The pattern showed 49% sensitivity, 81% specificity, and 64% accuracy, while BSTI criteria showed 51%, 77%, and 63%, respectively. Conclusion: Bilaterality, peripheral distribution of the predominant lung alteration, no pleural effusion, and perihilar vessels contour not blurred determine the most accurate COVID-19 pneumonia pattern. Lower field involvement, proposed by BSTI criteria, was not a distinctive finding. The BSTI criteria has lower specificity.